Geometric consideration of support structures in part overhang fabrications by electron beam additive manufacturing. (December 2015) - Cheng, Bo; Chou, Kevin
Abstract: Powder bed electron beam additive manufacturing (EBAM) has emerged as a potentially cost-effective process for high-value, small-batch productions for biomedical and aerospace applications. In EBAM, the process would not require support structures for overhang geometry because a build part is immersed in the powder bed. However, support structures are indeed needed in practice for an overhang; without it, the overhang area will have defects such as warping, which are due to the complex thermomechanical process in EBAM. In this study, a numerical approach is introduced to simulate the thermomechanical responses in the EBAM process of overhang structures. The objective of this study was to develop a 2D thermomechanical model, using a finite element method (FEM), to evaluate temperature induced deformation on different overhang support patterns in the EBAM process. The major results are summarized as follows. (1) The thermomechanical model is able to simulate the deformation of overhang parts in EBAM. The overhang length noticeably affects the overhang deformation. (2) As a traditional support structure, solid columns can reduce the overhang warping; further, the size of the column may be minimized to satisfy a deformation constraint, and meanwhile, reduce the amount of support materials. (3) Including a solid piece beneath the overhang, acting as a heat sink, may also reduce the overhang deformation; however, an appropriate gap must be incorporated so as not to fuse to the overhang area, while still effectively reducing the deformation. Highlights: The developed thermomechanical model is able to simulate the deformation of overhang parts in EBAM. The overhang length noticeably affects the overhang deformation. Solid columns can avoid a serious overhang warping defect. A solid piece beneath the overhang in the powder bed can reduce the overhang deformation.